Karakteristik Verba Aktivitas Bahasa Minangkabau: Pendekatan Makna Aspektualitas - Elvina A. Saibi; Iman Laili (Balai Bahasa Provinsi Bali, 2022)
The purpose of this study is to reveal the characteristic situation of activity verbs which emphasize the inherent aspectual meaning of verbs in verbal phrases as predicates. The situations expressed by the class of activity verbs have the characteristics of dynamic, atelic, durative, and nonhomogeneous situations. The method in this study uses a descriptive method and a structural approach, namely the principle of the unity of form and meaning is the starting point of the analysis. Furthermore, the data in this study are verbal phrases in the Minangkabau language which express the situation that occurs. The data source used comes from the Singgalang Newspaper published by West Sumatra, which uses the Minangkabau language. The data collection method is done by listening to the use of language. The technique used is note-taking technique. To analyze the data used distribution method. The techniques used in this study are expansion techniques, replacement techniques, and disappearance techniques. The results found in this research are incoative meaning, progressive meaning; continuative meaning, durative meaning, perfective meaning, iterative meaning, habituative meaning, and repetitive meaning. AbstrakTujuan penelitian ini mengungkapkan situasi karakteristik verba aktivitas yang menekankan pada makna aspektualitas inheren verba pada frasa verbal sebagai predikat. Situasi yang diungkapkan kelas verba aktivitas memiliki sifat-sifat situasi dinamis, atelik, duratif, dan nonhomogen. Metode dalam penelitian ini menggunakan metode deskriptif dan pendekatan struktural, yakni prinsip kesatuan bentuk dan makna merupakan titik tolak analisis. Selanjutnya, data dalam penelitian ini merupakan frasa verbal berbahasa Minangkabau yang mengungkapkan situasi yang terjadi. Sumber data yang digunakan bersumber dari Surat Kabar Singgalang terbitan Sumbar yang menggunakan bahasa Minangkabau. Metode pengumpulan data dilakukan dengan menyimak penggunaan bahasa. Teknik yang digunakan adalah teknik catat. Untuk menganalisis data digunakan metode agih. Teknik yang digunakan dalam penelitian ini merupakan teknik perluasan, teknik ganti, serta teknik lesap. Hasil yang ditemukan dalam penelitian ini adalah makna inkoatif, makna progresif; makna kontinuatif, makna duratif, makna perfektif, makna iteratif, makna habituatif, dan makna repetitif.